2022
DOI: 10.1002/clt2.12139
|View full text |Cite
|
Sign up to set email alerts
|

Total IgE in tears accurately reflects the severity and predicts the prognosis of seasonal allergic conjunctivitis

Abstract: Background Although immunoglobulin E (IgE) increases significantly in tears and serum during seasonal allergic conjunctivitis (SAC), it is unclear whether tear total IgE can reflect the severity and prognosis of SAC more accurately than serum total IgE. We aimed to investigate the usefulness of measuring the total IgE in tears to evaluate the severity and determine the treatment of SAC. Methods This prospective, nonrandomized study involved 55 patients with SAC and 10 age‐ and sex‐matched healthy controls. Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Regarding allergy test results, although Inada et al [21] and Mimura et al [33] state that t-tIgE levels are similar to s-tIgE levels, in this study, the proportion of s-tIgE positivity was lower than the proportion of t-tIgE positivity. (Table 3) It has also been reported that there was no correlation between t-tIgE and s-tIgE, and this may be due to the difference in severity of allergic conjunctivitis patients at general clinics and hospitals [34]. However, as reported [33,35] there is a relationship between positive t-tIgE and s-sIgE, this study also found a relationship between the two (Table 4).…”
Section: Discussionsupporting
confidence: 52%
“…Regarding allergy test results, although Inada et al [21] and Mimura et al [33] state that t-tIgE levels are similar to s-tIgE levels, in this study, the proportion of s-tIgE positivity was lower than the proportion of t-tIgE positivity. (Table 3) It has also been reported that there was no correlation between t-tIgE and s-tIgE, and this may be due to the difference in severity of allergic conjunctivitis patients at general clinics and hospitals [34]. However, as reported [33,35] there is a relationship between positive t-tIgE and s-sIgE, this study also found a relationship between the two (Table 4).…”
Section: Discussionsupporting
confidence: 52%
“…First, the serum IgE level was not measured because of its invasive procedure. Although it was reported that the total IgE concentration in the serum did not correlate with the severity of ocular symptoms (5) , this index should be involved in future research,…”
Section: Discussionmentioning
confidence: 95%
“…The traditional test methods of ACDs include the identification of eosinophils in the conjunctiva, instillation provocation test, and total IgE antibody measurements in the serum. 4 The total IgE antibody measurement in lacrimal fluid was reported to be helpful in the diagnosis and clinical evaluation of ACDs, 5 and several commercial kits are available in Europe and Japan. [6][7][8] However, simple and accurate diagnostic tests for ACDs remain absent from China.…”
mentioning
confidence: 99%
“…12,20 Also, CsA prevents the mitochondrial permeability transition (MPT) pore from opening by binding to cyclophilin D, which in turn increases the number of goblet cells and mucin secretion. 14,21 Other than that, CsA can reduce the allergic response by preventing mast cells (MCs) and basophils degranulation, and simultaneously suppressing eosinophil recruitment. 7 A recent study in mice suggested that calcineurin subunit A (CnAα) is involved in the early phases of mast cell-driven allergy reactions, and its de ciency resulted in the decrease of degranulation and in ammatory cytokines secretion in allergic responses.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Studies have revealed that total IgE in tears is a reliable predictor of the severity and prognosis of SAC patients. 14 Moreover, lymphotoxin-alpha (LT-α) is a member of the tumor necrosis factor (TNF)-related cytokines family, primarily generated by lymphocytes, which has been considered a diagnostic indicator for DE recently. 15 Apart from these, the primary relevant cytokines of ocular allergy and DE can be used as indicators of disease severity, such as IL-4, IL-5, IL-6, and TNF-α.…”
Section: Introductionmentioning
confidence: 99%